Role of Dilution Rate and Nutrient Availability in the Formation of Microbial Biofilms - Legner, Milos; McMillen, David R.; Cvitkovitch, Dennis G. (Frontiers in Microbiology, 2019)
We revisited the mathematical model of chemostat and examined consequences of considerably decreasing the concentration of limiting nutrient in the inflow for the growth of both the planktonic and biofilm cells in the chemostat tank (fermenter). The model predicts a substantially lower steady-state biomass of planktonic cells in response to decreasing inflowing nutrient concentration. Contrarily, the steady-state concentration of nutrient inside the fermenter is expected to remain the same, as long as the inflowing concentration does not fall below its value. That allows the biofilm cells to grow at a rate regulated only by the exchange rate of medium (dilution rate). This conclusion is supported by previously published data on pure and mixed cultures and by a current experiment with Enterococcus faecalis.